Chotosan, a Kampo Formula, Ameliorates Chronic Cerebral Hypoperfusion-Induced Deficits in Object Recognition Behaviors and Central Cholinergic Systems in Mice - Qi Zhao; Yukihisa Murakami; Michihisa Tohda; Ryosuke Obi; Yutaka Shimada; Kinzo Matsumoto (Elsevier, 2007)
We previously demonstrated that the Kampo formula chotosan (CTS) ameliorated spatial cognitive impairment via central cholinergic systems in a chronic cerebral hypoperfusion (P2VO) mouse model. In this study, the object discrimination tasks were used to determine if the ameliorative effects of CTS on P2VO-induced cognitive deficits are a characteristic pharmacological profile of this formula, with the aim of clarifying the mechanisms by which CTS enhances central cholinergic function in P2VO mice. The cholinesterase inhibitor tacrine (THA) and Kampo formula saikokeishito (SKT) were used as controls. P2VO impaired object discrimination performance in the object recognition, location, and context tests. Daily administration of CTS (750 mg/kg, p.o.) and THA (2.5 mg/kg, i.p.) improved the object discrimination deficits, whereas SKT (750 mg/kg, p.o.) did not. In ex vivo assays, tacrine but not CTS or SKT inhibited cortical cholinesterase activity. P2VO reduced the mRNA expression of m3 and m5 muscarinic receptors and choline acetyltransferase but not that of other muscarinic receptor subtypes in the cerebral cortex. Daily administration of CTS and THA but not SKT reversed these expression changes. These results suggest that CTS and THA improve P2VO-induced cognitive impairment by normalizing the deficit of central cholinergic systems and that the beneficial effect on P2VO-induced cognitive deficits is a distinctive pharmacological characteristic of CTS. Keywords:: chotosan, chronic cerebral hypoperfusion, object recognition memory deficit, cholinergic system, mouse model